POLARISASI PERSEPSI PARA PIHAK DALAM PENGEMBANGAN HOSPITALITAS EKOWISATA DI UNIT PENGELOLA WISATA KUBU TAMAN NASIONAL BUKIT BARISAN SELATAN (TNBBS) - Agustina Agustina; M. Winarno G. D; Darmawan A (Jurnal Hutan Tropis, 2018)
The perception stakeholders in the development of ecotourism in a destination is very important to learn. Alignment of perceptions of the stakeholders is needed to facilitate the implementation of various ecotourism activities. Differences in perception can be a barrier to the implementation of ecotourism development in Kubu Perahu tourist destination. This study aimed to determine the perceptions of three stakeholders (tourists, communities and managers) who will then be described in the form of polarization charts. Perceptions of stakeholders were obtained through questionnaire method (one score one indicator) and analyzed using descriptive analysis. The results of perceptions of stakeholders (tourists, communities and managers) in the development of ecotourism hospitality show a harmonious perception. Tourists have a good perception for all aspects of existing ecotourism hospitality in Kubu Perahu tourism. Communities and managers have a poor perception of one of the aspects of ecotourism hospitality in Kubu Perahu tourist destination is on the infrastructure aspect. The polarization of perceptions in general stakeholders (communities, tourists and managers) in the development of ecotourism hospitality shows a harmonious perception so that the form of symmetric polarization. It indicates that the management of tourism in Tourism Management Unit Kubu Perahu Taman Nasional Bukit Barisan Selatan (TNBBS) has been going well.Persepsi para pihak dalam pengembangan ekowisata di suatu destinasi sangat penting dipelajari. Keselarasan persepsi dari para pihak sangat dibutuhkan untuk memudahkan implementasi berbagai kegiatan ekowisata. Perbedaan persepsi dapat menjadi penghambat pelaksanaan pengembangan ekowisata di destinasi wisata Kubu Perahu. Penelitian ini bertujuan untuk mengetahui persepsi tiga stakeholders (wisatawan, masyarakat dan pengelola) yang kemudian akan digambarkan dalam bentuk bagan polarisasi. Persepsi stakeholders didapatkan melalui metode kuesioner (one score one indicator) dan dianalisis menggunakan analisis deskriptif. Hasil penelitian persepsi stakeholders (wisatawan, masyarakat dan pengelola) dalam pengembangan hospitalitas ekowisata menunjukkan persepsi yang selaras. Wisatawan memiliki persepsi yang baik untuk semua aspek hospitalitas ekowisata yang ada di destinasi wisata Kubu Perahu. Masyarakat dan pengelola memiliki peresepsi yang kurang baik terhadap salah satu aspek hospitalitas ekowisata di destinasi wisata Kubu Perahu yaitu pada aspek infrastruktur. Polarisasi persepsi secara umum stakeholders (wisatawan masyarakat dan pengelola) dalam pengembangan hospitalitas ekowisata menunjukkan persepsi yang selaras sehingga bentuk polarisasi simetris. Hal ini mengindikasikan bahwa pengelolaan wisata di Unit Pengelola Wisata Kubu Perahu Taman Nasional Bukit Barisan Selatan (TNBBS) sudah berjalan dengan baik.